Exploration of Managerial Competence in the Perspective of Pesenggiri Piil Scores and Its Implications on Teacher Performance - Yusuf, Muhammad; Muslimin; Ehwanudin; Midahayati, Rina (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study examines the integration of managerial competence with local cultural values in improving teacher performance at MTs Negeri 1 West Lampung. The background of this research is based on the importance of effective educational management that not only relies on formal managerial functions but also incorporates local wisdom as a contextual foundation for leadership. The study aims to explore how managerial competence based on Piil Pesenggiri values is implemented and its implications for teacher performance. This research uses a qualitative approach with a descriptive design. Data are collected through observation, in-depth interviews, and documentation involving the principal, teachers, and educational staff. The findings show that managerial competence integrated with Piil Pesenggiri values is implemented through planning, organizing, actuating, and controlling functions in a systematic and participatory manner. These values shape a collaborative, professional, and humanistic work culture that enhances teacher discipline, responsibility, motivation, and instructional quality. The study also finds that supporting factors include leadership commitment, positive organizational culture, and strong social cohesion, while obstacles arise from coordination issues and varying levels of value internalization among teachers. The conclusion indicates that the integration of managerial competence with local cultural values significantly contributes to improving teacher performance and creates a sustainable and value-based educational environment.